Optimized Image Watermarking Based On HD And SVD In IWT Domain - Ahmad Hisyam, Suryanto Sugian (2022)
In today's digital age, protecting the ownership of multimedia content has become a crucial issue. The widespread use of the internet and the ease of copying and distributing digital media have made it increasingly challenging to prevent unauthorized use and distribution. To address this problem, watermarking has emerged as an effective solution. Image watermarking refers to the process of embedding a unique identifier into an image in a way that it is imperceptible to the human eye but can be extracted to prove ownership. In this research, we propose an optimized image watermarking method based on Hessenberg Decomposition (HD) and Singular Value Decomposition (SVD) in the Integer Wavelet Transform (IWT) domain. The proposed method utilizes the HD feature of the image to enhance the robustness of the watermark against attacks, while the SVD technique is used to achieve high invisibility and security. The IWT domain is employed to make the watermarking process more efficient, leading to a faster and more reliable watermarking algorithm. To evaluate the effectiveness of the proposed method, we conducted several experiments using standard image datasets. The results show that the proposed method outperforms existing state-of-the-art watermarking methods in terms of robustness and invisibility. Additionally, the proposed method is resistant to various image processing attacks. In conclusion, the proposed optimized image watermarking method based on HD and SVD in the IWT domain offers a highly effective solution for protecting the ownership of multimedia content. The use of HD and SVD techniques in the IWT domain ensures high robustness, invisibility, and security of the watermark, while the computational efficiency of the method makes it practical for real-world applications.